Pengaruh Kualitas Sumber Daya Manusia Terhadap Kepuasan Wisatawan: Studi Kuantitatif di KEK Mandalika - Marswandi, Ega Dwi Putri; Ihyani, Layali; Marlina, Febria Nurmelia; Suhaeril, Suhaeril (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This study aims to determine the effect of the Quality of Human Resources on Tourist Satisfaction. The method used in this research. This research is quantitative which is explanatory in nature with a sample size of 35 respondents, namely employees in the Special Economic Zone area. Totaling 35 respondents, namely employees in the Special Economic Zone area of  Mandalika, Central Lombok Regency, West Nusa Tenggara Province. Method  data analysis method using simple linear regression test. Research results  stated that the quality of human resources affects tourist satisfaction positively and significantly. This is an input for decision makers  decision makers both for officials and apparatus of the Central Lombok Regency Tourism Office as well as decision makers of PT. officials and apparatus of the Central Lombok Regency Tourism Office as well as decision makers of PT Indonesia Tourism Development Corporation (ITDC) to continue to improve tourist satisfaction. Indonesia or Indonesia Tourism Development Corporation (ITDC) decision makers to continue to increase the visit of domestic and foreign tourists by continuing to improve the quality of human resources. improving the quality of human resources who have  literacy in serving tourists. Thus, it can create  comfort in the form of satisfaction which is reflected in the return visit of the tourists.